Peer attachment, coping, and self-esteem in institutionalized adolescents: the mediating role of social skills - Catarina Pinheiro Mota (2013)
This study analyzes the contribution of peer attachment in predicting active coping and self-esteem in a sample of 109 institutionalized adolescents. It also explores the mediating role of social skills in the association between peer attachment, coping, and self-esteem. Structural equation modeling identified a model able to predict a positive and direct contribution of peer relationships on self-esteem. Results confirmed the mediating role of social skills but only between quality of peer attachment and the development of active coping. From an ecological perspective, quality of relationships with significant peer figures can contribute to the development of a secure base, especially in adolescents without family support. Consequently, institutionalized adolescents who perceive quality in their peer relationships seem to be more able to express their feelings and ideas. As a result, they can become able to establish positive and empathic relationships with others, which can lead to the development of active coping skills. The quality of peer relationships can also increase the self-esteem of these adolescents because they feel they have a source of personal support and can share their difficulties.